Morning Serum Cortisol as a Predictor for the HPA Axis Recovery in Cushing’s Disease - Q. Cui; D. Liu; B. Xiang; Q. Sun; L. Fan; M. He; Y. Wang; X. Zhu; H. Ye (International Journal of Endocrinology)
Background. The suppressed hypothalamic-pituitary-adrenal (HPA) axis after successful surgery for Cushing’s disease (CD) will recover in almost all patients. We aimed to identify the predictive factors for HPA axis recovery in CD patients with postoperative remission. Design and Methods. This observational retrospective cross-sectional study enrolled 69 CD patients with postoperative remission in Huashan Hospital from 2015 to 2019. All subjects had a detailed clinical evaluation. The low-dose ACTH stimulation test (LDT) was conducted as the gold standard for assessing the HPA axis function. Results. Peak cortisol in LDT was found only to be positively correlative with morning serum cortisol (MSC) (ρ=0.451, p<0.001). The MSC was higher (p<0.001), and the median postoperative course was significantly longer (p=0.025) in the patients with the recovered HPA axis function compared with unrecovered patients. The AUC value of MSC for predicting the recovery of the HPA axis was 0.701, and the optimal cutoff was 6.25 μg/dl (sensitivity 85.19% and specificity 47.62%). Other useful cutoff values were 10.74 μg/dl (specificity 100%) and 4.18 μg/dl (sensitivity 100%). Besides, combined with the postoperative course, the AUC values were higher than MSC alone (0.935 vs. 0.701, p<0.001). Conclusions. MSC is a viable first-step diagnostic predictor for HPA axis recovery in CD patients with postoperative remission. For the patients with cortisol levels between 4.18 and 10.74 μg/dl, a confirmatory test should be conducted. When the MSC level was 10.74 μg/dl or greater, the replacement therapy could be discontinued.